2007
DOI: 10.1198/004017007000000245
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Bayesian Logistic Regression for Text Categorization

Abstract: Logistic regression analysis of high-dimensional data, such as natural language text, poses computational and statistical challenges. Maximum likelihood estimation often fails in these applications. We present a simple Bayesian logistic regression approach that uses a Laplace prior to avoid overfitting and produces sparse predictive models for text data. We apply this approach to a range of document classification problems and show that it produces compact predictive models at least as effective as those produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
513
0
7

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 639 publications
(522 citation statements)
references
References 36 publications
2
513
0
7
Order By: Relevance
“…Some recent studies Genkin et al 2006) have shown that some variations of Winnow and Bayesian regression are also very promising. Below, we compare the performance of several representative learning methods for authorship attribution.…”
Section: Machine Learning Approachmentioning
confidence: 99%
“…Some recent studies Genkin et al 2006) have shown that some variations of Winnow and Bayesian regression are also very promising. Below, we compare the performance of several representative learning methods for authorship attribution.…”
Section: Machine Learning Approachmentioning
confidence: 99%
“…10.3. The xml of this LU contains basic morpho-syntactic information (lines 3-8), some semantics (lines [11][12][13][14][15] and additional examples on the combinatorial behaviour of the word such as the lexical collocation de band oppompen (to inflate a tire) at line 41, and an idiomatic usage: uit de band springen (excessive behavior) at line 20.…”
Section: Lexical Unitsmentioning
confidence: 99%
“…Next, we used the patterns that were found by the machine learner to identify other word pairs that could be related by hypernymy. We used the same machine learner as [26]: Bayesian Logistic Regression [15].…”
Section: Acquisition Toolkit For Hypernym Pairsmentioning
confidence: 99%
“…The LASSO achieves accurate prediction by shrinking some coefficients and setting others to zero. A logistic regression version of the LASSO method was described by Genkin et al [13] in which the linear model where ≥ 0 is called the tuning parameter and  is the log-likelihood function:…”
Section: The Least Absolute Shrinkage and Selection Operator (Lasso)mentioning
confidence: 99%